Complications associated with the Rotarex® wire in a patient with peripheral artery disease. Issue 5 (24th May 2021) - Han, Donghoon; Shin, Dong‐Geum; Kang, Min‐Kyung; Rae Cho, Jung; Choi, Seonghoon; Lee, Namho; Lee, Jong‐Wook; Haeng Cho, Yoon
Abstract: The Rotarex ® device is used for thrombectomy as well as atherectomy in patients with PAD. It is important to carefully consider the wire position of the Rotarex ® device during the procedure. As possible as the wire should be located in a lesion‐free area. Abstract : The Rotarex ® device is used for thrombectomy as well as atherectomy in patients with PAD. It is important to carefully consider the wire position of the Rotarex ® device during the procedure. As possible as the wire should be located in a lesion‐free area.